(3Uhf GdefWb hGdcdGe Yf af GdefWb hGdcdGes - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3YHO GdQMef GdSjhWjs)
(3ChdgG (B:s
(3GdbGFd hbO JaQ GdfGS MJi CMOKhG GHOGYG aj GdOjf HGdQCj de JHYK HgG GdQSd MJi GSJMb HOjf Gddg CcKQge haj GdPj MedhG ef Ojfg TZd hbGd aj ehVY BNQ HGH eG LGA aj Re Gdbhd aj Ojf Gddg s
(3BNQgG (B:s
(3hcGfhG jQhf GONGd UfGYI aj CNQi EfeG jchf dLgd GdeJcde Ch dbUO GdeZGdWI hGdGSJQGMI HGdGfJbGd ef UfGYI Edi CNQi YfO Vjb GdcdGe Ydjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B2 / 1084s
(3TPQGJ GdPgH (B8 /15s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs